2011
DOI: 10.1155/2011/689524
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Nrf2-Regulated Glutathione Pathway Genes by Ischemic Preconditioning

Abstract: Prophylactic pharmacological activation of astrocytic gene expression driven by the transcription factor Nrf2 boosts antioxidant defences and protects against neuronal loss in ischemia and other disease models. However, the role of Nrf2 in mediating endogenous neuroprotective responses is less clear. We recently showed that Nrf2 is activated by mild oxidative stress in both rodent and human astrocytes. Moreover, brief exposure to ischemic conditions was found to activate Nrf2 both in vivo and in vitro, and thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 33 publications
1
62
0
1
Order By: Relevance
“…As ethical considerations do not allow for the use of brief repeated occlusion of the cerebral arteries to elicit stroke tolerance in humans, animal models of chemical preconditioning have been actively investigated in hopes to develop a clinically-useful approach to stroke preconditioning in humans. Moreover, chemical preconditioning may also be useful as a prophylactic approach to neuroprotection [11, 12]. The reason for this is that while the onset of stroke is often sudden and unpredictable, individuals with a higher than normal risk of stroke could benefit from prior measures that enhance the brain’s tolerance to potential ischemic injury.…”
Section: Introductionmentioning
confidence: 99%
“…As ethical considerations do not allow for the use of brief repeated occlusion of the cerebral arteries to elicit stroke tolerance in humans, animal models of chemical preconditioning have been actively investigated in hopes to develop a clinically-useful approach to stroke preconditioning in humans. Moreover, chemical preconditioning may also be useful as a prophylactic approach to neuroprotection [11, 12]. The reason for this is that while the onset of stroke is often sudden and unpredictable, individuals with a higher than normal risk of stroke could benefit from prior measures that enhance the brain’s tolerance to potential ischemic injury.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, depletion in glutathione content is associated with decreased xCT expression (Bell et al, 2011; Lewerenz et al, 2009). Ceftriaxone treatment was shown neuroprotection by inducing nuclear factor-erythroid 2-related factor (Nrf2)-mediated induction of xCT expression, leading to increase in intercellular glutathione levels (Bell et al, 2011; Lewerenz et al, 2009). A critical role of xCT has also been demonstrated in animal models of drug addiction.…”
Section: Introductionmentioning
confidence: 99%
“…The group Bell et al, demonstrated that pure neuronal cultures were unable to upregulate antioxidant genes under Nrf2-transcriptional control, suggesting that astrocytes are the primary source of Nrf2 production and activation. Finally, homozygous Nrf2 knockout mice were not protected from induction of IPC or exposure hydrogen peroxide following OGD, supporting the contributive role of Nrf2 to mediating IPC-induced neuroprotection [171].…”
Section: Nrf2mentioning
confidence: 83%